Ultratrace analysis for organolead compounds in Greenland snow. - Lobinski, Ryszard; Szpunar-Lobinska, Joanna; Adams, F. C. (HAL CCSD, 1994)
International audience A review, with 9 refs., of the anal. of snow and ice cores for organolead species by gas chromatog. with detection by microwave-induced plasma at. emission spectrometry, including sample handling and contamination control; the organolead species found in Greenland snow and ice; organolead compds. in ancient snow; and gasoline as a source of inorg. and org. Pb pollution in Greenland. [on SciFinder(R)]